Semiotika pada Novel Dompet Ayah Sepatu Ibu Karya Jombang Santani Khairen - Aisah Aisah; Dwi Wahyu Candra Dewi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to describe the mark in the novel Dompet Ayah Sepatu Ibu by Jombang santani Khairen published by PT Gramedia Widisarana. The novel totals 200 pages. The object of research is in the form of words, phrases, texts, and sentences in the content of the novel in the form of signs or symbols through a semiotic approach. The method used is a qualitative descriptive method, because data is described in words instead of numbers. Data collection techniques by reading, understanding, and recording important points are analyzed clearly. Data analysis techniques by sorting out data that are in accordance with the formulation of the problem studied in the research.